Correction: Structure–Function Parameters Over Different Surface Footprints in Coastal Zones - Andrey A. Grachev; Harindra J. S. Fernando; Stef L. Bardoel; Robb M. Randall; Christopher M. Hocut; Edward D. Creegan; Laura S. Leo (Boundary-Layer Meteorology, 2026)

Structural controls on lithium mineralization in shear-zone hosted granitic pegmatites of the Zulu pegmatite field, Zimbabwe – implications for exploration - Lot Koopmans; Nicholas J. Gardiner; Brayden St. Pierre; Richard M. Palin; Rutendo Musinga; Laurence J. Robb (Mineralium Deposita, 2026)
Granitic pegmatites are a significant source of critical metals including tin, tantalum, and most notably lithium. To meet future demand, a comprehensive exploration model is required to assist in the discovery of new hard rock deposits. Whereas recent work has largely focused on understanding the source and mineralization processes of pegmatites, the structural controls on the distribution and size of individual deposits remains poorly understood and understudied. In this contribution, we present a structural study on the Zulu pegmatite field in Zimbabwe, which provides a good example of the influence of shear zones, host rock rheology, and lithological competency contrasts on the orientation, size, and distribution of pegmatite bodies within a pegmatite field. At Zulu, we observe both structural and petrographic evidence for two types of pegmatite emplacement within an active shear zone during D 2 strike-slip dominated deformation. An early generation (Type 1) was emplaced syn-kinematic to D 2 within dilational jogs subparallel to the shear fabric, and continued ductile shearing also drove significant recrystallization which affected the primary magmatic phases and therefore influenced the preserved mineralogy. A later generation (Type 2) was emplaced syn-to-late-kinematic to D 2 along tension gashes and subordinate fracture sets oblique to the shear fabric, which served to truncate the cooling history and preserve a primarily magmatic mineralogy within this pegmatite group. By comparing Zulu to other large pegmatite deposits, we conclude that geologic structures are critical to source-to-sink connectivity in lithium pegmatite systems, and affect the mineralization potential of individual deposits by driving recrystallization. Assessing the structural history and relative timing of emplacement within a pegmatite field, in conjunction with detailed (micro)textural observations from within pegmatite bodies, is essential to understanding pegmatite emplacement geometries. A more systematic approach in constraining these relationships will therefore aid in generating new exploration targets in both greenfield and brownfield settings.

Structure–Function Parameters Over Different Surface Footprints in Coastal Zones - Andrey A. Grachev; Harindra J. S. Fernando; Stef L. Bardoel; Robb M. Randall; Christopher M. Hocut; Edward D. Creegan; Laura S. Leo (Boundary-Layer Meteorology, 2026)
High frequency turbulent data from sonic anemometers and other ancillary information collected at multiple levels on several meteorological flux towers located at two coastal sites are used to study velocity and scalar (temperature and humidity) structure–function parameters over heterogeneous surfaces in an area of complex coastal terrains. Understanding of such parameters has important applications for studies on wave propagation in a turbulent atmosphere. One observational site was located on the Outer Banks near the town of Duck, North Carolina, with data from the CASPER-East Program (October–November 2015). The second site was located near the town of Ferryland, Newfoundland, Canada, with data from the C-FOG (Coastal-Fog) field campaign (September–October 2018). These measurements allowed studies of structure parameters and other statistics for different footprints, including relatively smooth sea surface conditions and aerodynamically rough dry inland areas for both stable and unstable stratifications. The coastal land cover discontinuity for onshore and offshore winds leads to a thin internal boundary layer (IBL) that could often be resolved by the instrumented towers. The drag coefficient, Bowen ratio, and diurnal variation of sensible heat flux were found to be coastal IBL markers. Our study shows that lower values of the dimensional structure parameters are associated with higher altitudes, smooth surfaces (i.e., over water, outside onshore IBL) and stable stratification (e.g., nocturnal boundary layer), ceteris paribus. In particular, observations showed that the structure parameters over land footprint areas (inside the onshore IBL) can be an order of magnitude larger than over the sea surface due to the change of aerodynamic and thermal properties of the surface. This study also discusses the applicability of Monin–Obukhov similarity theory (MOST) for the velocity and scalar structure parameters in the coastal environment for both stable and unstable conditions. While surface inhomogeneities and the complexity of the coastal landforms nominally violate assumptions underlying MOST, our observations show that the nondimensional structure parameters obey MOST reasonably well for all measurement levels, stability condition, and wind direction. In addition, we suggest a new variance-based hybrid scaling for the structure parameters that overcomes some of the shortcomings of the traditional approach (e.g., self-correlation and ambiguity of the dimensionless temperature structure parameter for near-neutral conditions).

Three-dimensional management needs of deep-sea hydrothermal vent ecosystems - Sabine Gollner; Aline Jaeckel; Samantha Robb; Jozée Sarrazin; Verena Tunnicliffe; Jesse M.A. van der Grient; Diva J. Amon; Manuel Bellanger; Catherine Blanchard; Ana Colaço; Cherisse Du Preez; Patricia Esquete; et al. (Marine Policy, 2026)

Potential strategic ore deposits on Mars: Implications for in situ resource utilization - Richard M. Palin; Laurence Robb; Nicholas J. Gardiner; Lot Koopmans; Felix Sihombing; Mohammad Sayab; Jon Wade; Stephen M. Elardo (Earth-Science Reviews, 2025)

The magmatic-hydrothermal transition recorded by trace elements in quartz: a case study from the Zaaiplaats Tin Field, South Africa - L. C. Vonopartis; P. A. M. Nex; J. A. Kinnaird; L. J. Robb; R. Bolhar (Mineralium Deposita, 2025)
The composition of quartz has historically been considered unimportant for mineral exploration, although this perspective is changing with the advancement of analytical techniques. The ability to measure trace element variations in quartz provides a unique window into the evolution of mineral deposits. Granites are currently of interest as they can host late-stage magmatic-hydrothermal mineralisation, such as Sn and other critical metals. The Nebo, Bobbejaankop, and Lease granites in the Zaaiplaats Tin Field of the Bushveld Complex represent well-exposed expressions of endogranitic Sn-mineralisation. These granites display an upward increase in their degree of hydrothermal alteration. Disseminated Sn-mineralisation is restricted to the Bobbejaankop and Lease granites and high-grade cassiterite-bearing tourmaline-quartz hydrothermal pipes that radiate upwards through these granites, terminating below the roof contact. Trace element compositions of the quartz from the Zaaiplaats Tin Field shows evidence that supports the suggested fractionation and fluid-saturation models of ore genesis. The Al/Ti and Ge/Ti ratios in quartz increase from the base to the roof and illustrate the sequential fractionation and increase in the degree of fluid-rock interaction. The trace element data display a shift from a magmatic fractionation-controlled evolution to a hydrothermally-controlled system influenced by the saturation of a late-stage magmatic-hydrothermal fluid. Thus, trace element variations in quartz can record the point of fluid-saturation and the magmatic-hydrothermal transition. Therefore, the recognition of the most evolved, fluid-saturated facies indicates lithologies with the best mineralisation potential for cassiterite. The use of trace elements in quartz extends beyond granite-hosted deposits and is potentially applicable to various mineralised systems.

Resistance training, but not leucine, increased basal muscle protein synthesis and reversed frailty in older women consuming optimized protein intake - Kathryn J. Jacob; Guy Hajj-Boutros; Vita Sonjak; Jean-Phillippe Leduc-Gaudet; Felipe Broering; Charles Robb Flynn; Stéphanie Chevalier; Marie Lamarche; Sabah N. A. Hussain; José A. Morais (GeroScience, 2025)
Frailty, often linked to sarcopenia, involves reduced muscle strength and mass. While sarcopenia has multiple causes, impaired muscle protein synthesis may contribute. Leucine and resistance training (RT) are anabolic stimuli, but the long-term effects of leucine combined with RT in pre/frail older women remain unclear. This double-blind, placebo-controlled study aimed to assess their impact on muscle anabolism and characteristics in women consuming adequate protein. Pre/frail elderly women ( n = 19, 77.5 ± 1.3 y, BMI: 25.1 ± 0.9 kg/m 2 ), underwent 12 weeks of RT with protein-optimized diet (1.2 g ⋅ kg BW −1 ⋅ d −1 ) and were randomized to 7.5 g/d of leucine (Leu) or placebo 5.1 g/d alanine (Ala). The primary outcome was myofibrillar fractional synthesis rate (MyoFSR) in the postabsorptive and postprandial states. Secondary outcomes are changes in protein content and expression, 1-repetition maximum, body composition (DXA), and myofiber profiles were investigated. Overall MyoFSR increased by 47%, with a concomitant increase in type 1 and 2a myofiber cross sectional area (CSA) (16% and 28%, respectively), and total lean mass (2%). Total AKT, S6, and AMPKα levels were unchanged. However, AKT and S6 phosphorylation increased postprandially before RT, with no change following RT. The number of Frailty Criteria was reduced by 64%, with improvements in physical function and strength. Leucine had no added anabolic benefit. RT with optimal protein intake significantly improved the Frailty Phenotype and increased basal MyoFSR along with type 1 and 2a myofiber CSA and total lean mass, with no added benefit of leucine supplementation.

Global overview of national regulations for antibiotic use in aquaculture production - Ola Luthman; Dave H. F. Robb; Patrik J. G. Henriksson; Peter S. Jørgensen; Max Troell (Aquaculture International, 2024)
The intensification of aquaculture industries around the globe has led to increased susceptibility and exposure to diseases. To ensure the well-being of animals and the profitability of the industry, many aquaculture farms resort to antibiotic treatments. However, with the increasing presence of antimicrobial resistance (AMR), it has become important to regulate and limit the use of antibiotics, especially in animal production and regarding the antibiotics that are deemed as critically important for human health by the World Health Organization (WHO). This review describes how AMR mitigation strategies have developed over time in international settings and how they relate to aquaculture. Furthermore, we analyzed how different countries and regions abide by these statutes, as well as the antibiotic standards from a selection of certification schemes. Our results show that the role of aquaculture has been inexplicitly addressed in international guidance documents and that there is a need to further increase the activities of aquaculture operations in combating AMR, with an emphasis on alternatives to antibiotic use. We also found that most countries and regions allow the highest priority-, or critically important antibiotics in aquaculture, which could have detrimental effects on animal, environmental, and public health. As a result, most countries fail to comply with the recommendations and standards set by international organizations and certification schemes.

On tin and lithium granite systems: A crustal evolution perspective - Nicholas J. Gardiner; Richard M. Palin; Lot Koopmans; Martin F. Mangler; Laurence J. Robb (Earth-Science Reviews, 2024)

TOB1 and TOB2 mark distinct RNA processing granules in differentiating lens fiber cells - Rafaela C. Perez; Xenia Yang; Mary Familari; Gemma Martinez; Frank J. Lovicu; Gary R Hime; Robb U de Iongh (Journal of Molecular Histology, 2024)

Revisiting the timing of Saginaw lobe ice retreat and implications for drainage adjustments across southern Michigan, USA - Nathan R. Erber; Alan E. Kehew; Randall J. Schaetzl; Robb Gillespie; Mohamed E. Sultan; John Esch; John Yellich; B. Brandon Curry; Sebastien Huot; Abotalib Z. Abotalib (CATENA, 2023)

Fish Erythrocyte Extracellular Traps (FEETs) are an evolutionarily conserved cellular process triggered by different stimuli - Giulia Rinaldi; Neila Álvarez de Haro; Anuruddika J. Fernando; Andrew P. Desbois; Calum T. Robb; Adriano G. Rossi (Fish & Shellfish Immunology, 2023)

Rapid SNP genotyping, sex identification, and hybrid-detection in threatened bull trout - Stephen J. Amish; Shana Bernall; Patrick DeHaan; Michael Miller; Sean O’Rourke; Matthew C. Boyer; Clint Muhlfeld; Angela Lodmell; Robb F. Leary; Gordon Luikart (Conservation Genetics Resources, 2022)

Micromorphological investigations at Scaloria Cave (Puglia, South-east Italy): new evidences of multifunctional use of the space during the Neolithic - I. Rellini; M. Firpo; E. Isetti; G. Rossi; J. Robb; D. Pian; A. Traverso (Archaeological and Anthropological Sciences, 2020)

No evidence for ecological segregation protecting native trout from invasive hybridization - Ryan P. Kovach; Clint C. Muhlfeld; Robert Al‐Chokhachy; Stephen J. Amish; Jeffrey L. Kershner; Robb F. Leary; Winsor H. Lowe; Gordon Luikart; Phil Matson; David A. Schmetterling; Bradley B. Shepard; Peter A. H. Westley; et al. (Global Change Biology, 2017)

Legacy introductions and climatic variation explain spatiotemporal patterns of invasive hybridization in a native trout - Clint C. Muhlfeld; Ryan P. Kovach; Robert Al‐Chokhachy; Stephen J. Amish; Jeffrey L. Kershner; Robb F. Leary; Winsor H. Lowe; Gordon Luikart; Phil Matson; David A. Schmetterling; Bradley B. Shepard; Peter A. H. Westley; et al. (Global Change Biology, 2017)
Hybridization between invasive and native species, a significant threat to worldwide biodiversity, is predicted to increase due to climate‐induced expansions of invasive species. Long‐term research and monitoring are crucial for understanding the ecological and evolutionary processes that modulate the effects of invasive species. Using a large, multidecade genetics dataset ( N = 582 sites, 12,878 individuals) with high‐resolution climate predictions and extensive stocking records, we evaluate the spatiotemporal dynamics of hybridization between native cutthroat trout and invasive rainbow trout, the world's most widely introduced invasive fish, across the Northern Rocky Mountains of the United States. Historical effects of stocking and contemporary patterns of climatic variation were strongly related to the spread of hybridization across space and time. The probability of occurrence, extent of, and temporal changes in hybridization increased at sites in close proximity to historical stocking locations with greater rainbow trout propagule pressure, warmer water temperatures, and lower spring precipitation. Although locations with warmer water temperatures were more prone to hybridization, cold sites were not protected from invasion; 58% of hybridized sites had cold mean summer water temperatures (

Behavioural response to song and genetic divergence in two subspecies of white‐crowned sparrows ( Zonotrichia leucophrys ) - Sara E. Lipshutz; Isaac A. Overcast; Michael J. Hickerson; Robb T. Brumfield; Elizabeth P. Derryberry (Molecular Ecology, 2017)
Divergence in sexual signals may drive reproductive isolation between lineages, but behavioural barriers can weaken in contact zones. Here, we investigate the role of song as a behavioural and genetic barrier in a contact zone between two subspecies of white‐crowned sparrows ( Zonotrichia leucophrys ). We employed a reduced genomic data set to assess population structure and infer the history underlying divergence, gene flow and hybridization. We also measured divergence in song and tested behavioural responses to song using playback experiments within and outside the contact zone. We found that the subspecies form distinct genetic clusters, and demographic inference supported a model of secondary contact. Song phenotype, particularly length of the first note (a whistle), was a significant predictor of genetic subspecies identity and genetic distance along the hybrid zone, suggesting a close link between song and genetic divergence in this system. Individuals from both parental and admixed localities responded significantly more strongly to their own song than to the other subspecies song, supporting song as a behavioural barrier. Putative parental and admixed individuals were not significantly different in their strength of discrimination between own and other songs; however, individuals from admixed localities tended to discriminate less strongly, and this difference in discrimination strength was explained by song dissimilarity as well as genetic distance. Therefore, we find that song acts as a reproductive isolating mechanism that is potentially weakening in a contact zone between the subspecies. Our findings also support the hypothesis that intraspecific song variation can reduce gene flow between populations.

Life Cycle Impacts of Natural Fiber Composites for Automotive Applications: Effects of Renewable Energy Content and Lightweighting - Claire S. Boland; Robb De Kleine; Gregory A. Keoleian; Ellen C. Lee; Hyung Chul Kim; Timothy J. Wallington (Journal of Industrial Ecology, 2016)
Summary This study examines the life cycle energy demand and greenhouse gas (GHG) emissions associated with substituting natural cellulose and kenaf in place of glass fibers in automotive components. Specifically, a 30 wt% glass‐fiber composite component weighing 3 kilograms (kg) was compared to a 30 wt% cellulose fiber composite component (2.65 kg) and 40 wt% kenaf fiber composite component (2.79 kg) for six cars, crossovers, and sport utility vehicles. The use‐phase fuel consumption of the baseline and substitute components, with and without powertrain resizing, were determined using a mass‐induced fuel consumption model based on U.S. Environmental Protection Agency test records. For all vehicles, compared to the baseline glass fiber component, using the cellulose composite material reduced life cycle energy demand by 9.2% with powertrain resizing (7.2% without) and reduced life cycle GHG emissions by 18.6% with powertrain resizing (16.3% without), whereas the kenaf composite component reduced energy demand by 6.0% with powertrain resizing (4.8% without) and GHG emissions by 10.7% with powertrain resizing (9.2% without). For both natural fiber components, the majority of the life cycle energy savings is realized in the use‐phase fuel consumption as a result of the reduced weight of the component.

A Semi-Automated, Multi-Source Data Fusion Update of a Wetland Inventory for East-Central Minnesota, USA - Steven M. Kloiber; Robb D. Macleod; Aaron J. Smith; Joseph F. Knight; Brian J. Huberty (Wetlands, 2015)

HLA class I, KIR, and genome-wide SNP diversity in the RV144 Thai phase 3 HIV vaccine clinical trial - Heather A. Prentice; Philip K. Ehrenberg; Karen M. Baldwin; Aviva Geretz; Charla Andrews; Sorachai Nitayaphan; Supachai Rerks-Ngarm; Jaranit Kaewkungwal; Punnee Pitisuttithum; Robert J. O’Connell; Merlin L. Robb; Jerome H. Kim; et al. (Immunogenetics, 2014)

Metallogeny of precious and base metal mineralization in the Murchison Greenstone Belt, South Africa: indications from U–Pb and Pb–Pb geochronology - J. Jaguin; M. Poujol; P. Boulvais; L. J. Robb; J. L. Paquette (Mineralium Deposita, 2012)

Influence of translocation strategy and mating system on the genetic structure of a newly established population of island ptarmigan - Andrew J. Gregory; Robb S. A. Kaler; Thomas J. Prebyl; Brett K. Sandercock; Samantha M. Wisely (Conservation Genetics, 2012)

Does food supplementation really enhance productivity of breeding birds? - Timothy J. E. Harrison; Jennifer A. Smith; Graham R. Martin; Dan E. Chamberlain; Stuart Bearhop; Gillian N. Robb; S. James Reynolds (Oecologia, 2010)

The effect of marker choice on estimated levels of introgression across an avian (Pipridae: Manacus ) hybrid zone - TAMAKI YURI; ROBERT W. JERNIGAN; ROBB T. BRUMFIELD; NIRMAL K. BHAGABATI; MICHAEL J. BRAUN (Molecular Ecology, 2009)
Hybrid zones are often characterized by narrow, coincident clines for diverse traits, suggesting that little introgression occurs across them. However, this pattern may result from a bias in focussing on traits that are diagnostic of parental populations. Such choice of highly differentiated traits may cause us to overlook differential introgression in nondiagnostic traits and to distort our perception of hybrid zones. We tested this hypothesis in an avian hybrid zone by comparing cline structure in two sets of molecular markers: isozyme and restriction fragment length polymorphism markers chosen for differentiation between parental forms, and microsatellite markers chosen for polymorphism. Two cline‐fitting methods showed that cline centre positions of microsatellite alleles were more variable than those of isozyme and restriction fragment length polymorphism markers, and several were significantly shifted from those of the diagnostic markers. Cline widths of microsatellite alleles were also variable and two‐ to eightfold wider than those of the diagnostic markers. These patterns are consistent with the idea that markers chosen for differentiation are more likely to be under purifying selection, and studies focussed on these markers will underestimate overall introgression across hybrid zones. Our results suggest that neutral and positively selected alleles may introgress freely across many hybrid zones without altering perceived boundaries between hybridizing forms.

Spatial scales of variance in abundance of intertidal species: effects of region, dispersal mode, and trophic level - Michael T. Burrows; Robin Harvey; Linda Robb; Elvira S. Poloczanska; Nova Mieszkowska; Pippa Moore; Rebecca Leaper; Stephen J. Hawkins; Lisandro Benedetti-Cecchi (Ecology, 2009)
Determination of the pattern of variation in population abundance among spatial scales offers much insight into the potential regulating factors. Here we offer a method of quantifying spatial variance on a range of scales derived by sampling of irregularly spaced sites along complex coastlines. We use it to determine whether the nature of spatial variance depends on the trophic level or the mode of dispersal of the species involved and the role of the complexity of the underlying habitat. A least‐cost distance model was used to determine distances by sea between all pairs of sites. Ordination of this distance matrix using multidimensional scaling allowed estimation of variance components with hierarchical ANOVA at nested spatial scales using spatial windows. By repeatedly moving these spatial windows and using a second set of spatial scales, average variance scale functions were derived for 50+ species in the UK rocky intertidal. Variance spectra for most species were well described by the inverse power law (1/ f β ) for noise spectra, with values for the exponent ranging from 0 to 1.1. At higher trophic levels (herbivores and carnivores), those species with planktonic dispersal had significantly higher β values, indicating greater large‐ than small‐scale variability, as did those on simpler coastlines (southwestern England and Wales vs. western Scotland). Average abundance and proportional incidence of species had the strongest influence on β values, with those of intermediate abundance and incidence having much greater large‐scale variance (β ≈ 0.5) than rare or ubiquitous species (β ≈ 0).

Rainbow Smelt (Osmerus mordax) Genomic Library and EST Resources - K. R. von Schalburg; J. Leong; G. A. Cooper; A. Robb; M. R. Beetz-Sargent; R. Lieph; R. A. Holt; R. Moore; K. V. Ewart; W. R. Driedzic; B. F. H. ten Hallers; B. Zhu; et al. (Marine Biotechnology, 2008)
Genomic resources in rainbow smelt ( Osmerus mordax ) enable us to examine the genome duplication process in salmonids and test hypotheses relating to the fate of duplicated genes. They further enable us to pursue physiological and ecological studies in smelt. A bacterial artificial chromosome library containing 52,410 clones with an average insert size of 146 kb was constructed. This library represents an 11-fold average coverage of the rainbow smelt ( O. mordax ) genome. In addition, several complementary deoxyribonucleic acid libraries were constructed, and 36,758 sequences were obtained and combined into 12,159 transcripts. Over half of these transcripts have been identified, several of which have been associated with cold adaptation. These basic resources show high levels of similarity (86%) to salmonid genes and provide initial support for genome duplication in the salmonid ancestor. They also facilitate identification of genes important to fish and direct us toward new technologies for other studies in fish biology.

Expansion of the genomics research on Atlantic salmon Salmo salar L. project (GRASP) microarray tools - K. R. VonSchalburg; G. A. Cooper; J. Leong; A. Robb; R. Lieph; M. L. Rise; W. S. Davidson; B. F. Koop (Journal of Fish Biology, 2008)
Salmonids are the most widely studied group of fish, and in the last few years, genomics technologies have begun to contribute to this rich biology. The first salmonid microarrays appeared in 2004 and since then several dozen studies have demonstrated the utility of genomic approaches. The widespread use of the genomics research on Atlantic salmon project 16 k array and greatly expanded genome resources have led to the development of an experimental 5 k oligo (70‐mer) array and a 32 k cDNA microarray in the near future. In this paper, the authors examined some of the procedures used in the development of past arrays and reexamined them in light of new genomic data available. Some preliminary control experiments of the new 5 k array were investigated that examine oligo designs based on distance from the polyA tail, the effects of mismatches and cross‐species hybridization specificity. Beneficial approaches are also identified in the development of the new 32 k cDNA array.

Very high incidence of familial colorectal cancer in Newfoundland: a comparison with Ontario and 13 other population-based studies - R. C. Green; J. S. Green; S. K. Buehler; J. D. Robb; D. Daftary; S. Gallinger; J. R. McLaughlin; P. S. Parfrey; H. B. Younghusband (Familial Cancer, 2007)

Coxsackievirus replication and the cell cycle: a potential regulatory mechanism for viral persistence/latency - Ralph Feuer; Ignacio Mena; Robb R. Pagarigan; Daniel E. Hassett; J. Lindsay Whitton (Medical Microbiology and Immunology, 2004)

Role of heparan sulfate in interactions of Listeria monocytogenes with enterocytes - Michelle J. Henry-Stanley; Donavon J. Hess; Elizabeth A. Erickson; Robb M. Garni; Carol L. Wells (Medical Microbiology and Immunology, 2003)

The RadB protein from Pyrococcus does not complement E. coli recA mutations in vivo - W. Inwood; S. Kane; J. DiRuggiero; F. Robb; A.J. Clark (Molecular Genetics and Genomics, 2001)

Novel structure and redox chemistry of the prosthetic groups of the iron-sulfur flavoprotein sulfide dehydrogenase from Pyrococcus furiosus; evidence for a [2Fe-2S] cluster with Asp(Cys)3 ligands - W. R. Hagen; P. J. Silva; M. A. Amorim; P.-L. Hagedoorn; H. Wassink; H. Haaker; F. T. Robb (JBIC Journal of Biological Inorganic Chemistry, 2000)

Cholinergic neurotransmission influences covert orientation of visuospatial attention in the rat - Janice M. Phillips; Kerry McAlonan; William G.K. Robb; Verity J. Brown (Psychopharmacology, 2000)

K-Ar dating of white micas from the Ventersdorp Contact Reef of the Witwatersrand Basin, South Africa: timing of post-depositional alteration - B. Zhao; N. Clauer; L. J. Robb; H. Zwingmann; T. Toulkeridis; F. M. Meyer (Mineralogy and Petrology, 1999)

Characteristics of post-depositional fluids in the Witwatersrand Basin - G. R. Drennan; M. -C. Boiron; M. Cathelineau; L. J. Robb (Mineralogy and Petrology, 1999)

Scalp-Recorded EEG Localization in MRI Volume Data - Benjamin H. Brinkmann; Terence J. O'Brien; M. Alex Dresner; Terrence D. Lagerlund; Frank W. Sharbrough; Richard A. Robb (Brain Topography, 1998)

Pyrococcus horikoshii sp. nov., a hyperthermophilic archaeon isolated from a hydrothermal vent at the Okinawa Trough - Juan M. González; Yaeko Masuchi; F. T. Robb; James W. Ammerman; Dennis L. Maeder; Miki Yanagibayashi; J. Tamaoka; Chiaki Kato (Extremophiles, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Development of PCR-based diagnostics for soil borne plant pathogens - R. N. Nazar; E. J. Robb; X. Hu; T. Volossiouk; S. W. Lee (Journal of Plant Biology, 1997)

Purification and regulation of glutamine synthetase in a collagenolytic Vibrio alginolyticus strain - Sandhya J. Bodasing; Paul W. Brandt; Frank T. Robb; David R. Woods (Archives of Microbiology, 1985)

Dynamic computer-generated displays of data from biplane roentgen angiography for study of the left ventricle - J. F. Greenleaf; E. L. Ritman; E. H. Wood; R. A. Robb; S. A. Johnson (Annals of Biomedical Engineering, 1974)

Silver plate for potatoes - C. J. Robb (American Journal of Potato Research, 1959)

Seasonal tendencies in the potato market during the kaw valley shipping season - E. A. Stokdyk; Daniel Dean; F. G. Robb; S. J. Wellensiek; W. A. McCubbin; C. L. Fitch; H. O. Werner (American Journal of Potato Research, 1925)